CompTIA Linux+ study guide: Exam XK0-005 - Blum, Richard, 1962-; Bresnahan, Christine (Sybex, a Wiley brand, 2022)
"The best-selling, hands-on roadmap to acing the new Linux+ exam In the newly updated Fifth Edition of CompTIA Linux+ Study Guide: Exam XK0-005, IT industry veterans and tech education gurus Richard Blum and Christine Bresnahan deliver a concise and practical blueprint to success on the CompTIA Linux+ exam and in your first role as a Linux network or system administrator. In the book, you'll find concrete strategies and proven techniques to master Linux system management, security, scripting, containers, automation, and troubleshooting. Every competency tested on the Linux+ exam is discussed here. You'll also get: Hands-on Linux advice that ensures you're job-ready on the first day of your new network or sysadmin role Test-taking tips and tactics that decrease exam anxiety and get you ready for the challenging Linux+ exam Complimentary access to the Sybex learning environment, complete with online test bank, bonus practice exams, electronic flashcards, and a searchable glossaryPerfect for practicing network and system admins seeking an in-demand and valuable credential for working with Linux servers and computers, CompTIA Linux+ Study Guide: Exam XK0-005, Fifth Edition, will also earn a place in the libraries of people looking to change careers and start down an exciting new path in tech."--